Analisis Perencanaan Strategis Program CERDIG (Cerdas Digital) Kominfo Jawa Timur dalam Pencegahan Judi Online - Fitria Widiyani Roosinda; Ariyan Alfraita; Widya Anggraeni (CV. ITTC INDONESIA, 2026)
This study aims to analyze the strategic planning of the CERDIG (Digital Intelligence) Program implemented by the East Java Provincial Ministry of Communication and Information Technology (Kominfo) as a Preventative measure to combat online gambling through education. This research method uses a descriptive qualitative approach with the theory of Strategic Planning for Relations by Ronald D. Smith. The results show that the communication strategy implemented thorugh outreach, webinars, and cross-agency collaboration to raise public awareness about the risks of online gambling. This program targets schoolchildren, university students, and the general public to build awareness and be more wise in using digital technology. In conclusion, although the education program has been running well, ongoing evaluation of changes in community behavior and more measurable measurement of the direct impact on reducing online gambling rates in East Java are still needed.